Energy efficiency consultants as change agents? Examining the reasons for EECs' limited success - Daniel Feser; Petrik Runst (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2015)
Residential energy consumption has been increasingly singled out by public policies as a key area for potential emission reduction. The public implementation of energy efficiency consultants (EECs) as change agents aims at the diffusion of innovation in building efficiency and overcoming information asymmetries in the construction sector. However, the success of these measures has been described as low. We conducted a case study involving 17 in-depth expert interviews to examine the causes of this failure within the German institutional context. This analysis has important implications for EECs in general and other European countries. We show that credence good characteristics in the ECC market led to a low willingness to pay. Certification of EECs does not suffice to overcome information asymmetries. We also identify a mismatch between EECs and customer incentives. As top-down policies have failed to facilitate a viable EEC market, we recommend a greater role for private and private-public networks, the cutting of EEC subsidies and a closer alignment between climate policy goals and home owners' economic efficiency considerations. – – Der Energieverbrauch von Wohnhäusern stellt eine wichtige Zielgröße der deutschen Politik dar, um die CO2 Emissionen langfristig zu senken. Die Förderung von Energieberatungen ist darauf ausgerichtet, innovatives Wissen unter Hauseigentümern zu verbreiten und potentielle Informationsasymmetrien im Sanierungsmarkt zu überwinden. Der Erfolg dieser Maßnahmen ist allerdings fragwürdig. Wir führen 17 Experteninterviews durch, um zu untersuchen, unter welchen Problemen der Energieberatermarkt leidet. Wir zeigen, dass der Energieberatermarkt von starken Informationsasymmetrien geprägt ist, die die Herausbildung eines Vertrauensverhältnisses erschwert. Die Zahlungsbereitschaft der Kunden ist niedrig. Wir identifizieren außerdem eine Diskrepanz zwischen den Anreizen der Berater (Energie sparen) und der Kunden (Kosten minimieren). Unsere Ergebnisse legen nahe, dass die Förderung von Energieberatungen ihr Ziele verfehlt. Weiterhin empfehlen wir die Stärkung von privaten und halb-öffentlichen Netzwerken und eine verbesserte Anpassung der Energiepolitik an die Bedürfnisse der Hausbesitzer.
Keywords: 330; asymmetric information; credence goods; labeling; change agents; energy audits